A Naturalistic Study of the Maintenance of Gains Made With Treatment of Patients With Profound Treatment-Refractory Obsessive-Compulsive Disorder - Nadeem, Nighat Jahan; Chan, Emily; Drummond, Lynne (Frontiers in Psychiatry, 2021)
Obsessive-compulsive disorder (OCD) generally responds to first-line treatment but patients often relapse. The United Kingdom National OCD Inpatient Service treats patients who have failed to respond to at least 2 trials of SRI, augmented with a dopamine blocker and 2 trials of ERP. Despite this, they have profound treatment-refractory OCD and require 24-hour nursing care due to severe OCD. We examined patients’ Y-BOCS score on admission, discharge and at each follow-up from all patients discharged over 5 years (02/01/2014-31/12/18). Data were analysed using SPSS. Paired student t-tests were used to assess improvement from admission to discharge and each follow-up. Over 5 years, 130 adult patients were treated: 79 male and 51 female with an average age of 42.3 years (20-82; sd14.4). Their ethnic backgrounds were; 115 Caucasian, 11 South Asian, 1 Chinese and 3 Unspecified. On admission, the average Y-BOCS total score was 36.9 (30-40; sd2.6). At discharge, patients had improved on average by 36% (Y-BOCS reduction to 23.4=moderate OCD). Similar reduction in Y-BOCS continued throughout the year with an average Y-BOCS of 22.9 at 1 month (n=69); 23 at 3 months (n=70); 21.3 at 6 months (n=78) and 21.9 at one year (n=77). Twenty-seven patients did not attend any follow-up appointment whilst others attended at least one appointment with the majority attending more than 3. Using student t-test, improvements at discharge, 1, 3, 6 and 12 months post-treatment showed a highly significant improvement (p<0.001). Gains made following inpatient treatment for treatment-refractory OCD were generally maintained until 1 year post-treatment.